Being a Roman citizen - Gardner, Jane F. (Routledge, 1993)
This is a book about Roman law for Roman historians. It reveals that the rules stated baldly in legal textbooks had a real and active function in maintaining the fabric of Roman society. As well as references to legal texts and literary sources, it makes use of epigraphic material, including recent finds in Italy and Spain, and of significant finds from Pompeii which show law in action in the commercial life of Puteoli. The rights and duties of Roman citizens in private life were affected by certain basic differences in their formal status. Women, ex-slaves, adults with living fathers, convicted criminals, play-actors - even the blind, deaf and dumb, and the mentally ill - although all were citizens, they were far from having equal legal rights and capacities. Jane F. Gardner examines in detail what the particular legal disabilities were which affected each group and also what the practical implications of these were for the conduct of daily life. She also considers whether and how they may be related to the distinctively Roman institution of patria potestas, and to direct personal participation and interaction, which was a requirement for most transactions with legal consequences for persons and property. In Being a Roman Citizen Jane F. Gardner sheds new light on Roman citizenship and challenges common assumptions about the reasons for discrimination between individuals and about the social attitudes implied.